Synthesis and Crystal Structure of One-Dimensional Linear Supramolecular Tetraazamacrocyclic Nickel(II) Complex - Bi, Jian-Hong; Xia, Hong; Huang, Zi-Xiang (Asian Journal of Chemistry, 2010)
The nickel(II) complex [NiL]·(ClO4)2 (L = 5,5,7,12,12, 14-hexamethyl-1,4,8,11-tetraazacyclotetradeca-4,11-diene) has been synthesized and its crystal structure was determined by X-ray diffraction. The crystal is monoclinic, space group P2(1)/c, a = 10.2600(8) Å, b = 10.7600(5) Å, c = 10.9000(7) Å, α = 90º, β = 111.410(2)º, γ = 90º, V = 1120.29(12) Å3, Mr = 538.07, Z = 2, Dc = 1.595 g/cm3, F(1000) = 564, I = 1.155 mm-1. The final R = 0.0336 and wR = 0.0880 for 2517 observed reflections (I > 2σ(I)). The center nickel(II) ion is coordinated by four N atoms in a little distortion plane square geometry. The compound is in one-dimensional linear supramolecular state.